Avaliação ultrassonográfica hepática ao modo-B, dúplex e tríplex Doppler de cães com sobrepeso e obesos - Belotta, Alexandra Frey [UNESP] (2015)
Veterinary care of overweight and obese dogs in small animal clinical sciences has become increasingly common. The aim of the present study was to investigate, using two dimensional and Doppler sonography, parenchymal and hemodynamic changes in three groups of dogs, according to body score condition (G1, ideal body weight/control; G2, overweight; G3, obese), without hepatic diseases due to other causes. A positive correlation was found between G3 and the characteristics described below: increased liver echogenicity, hepatomegaly, hiperlipidemia and abnormal hepatic vein Doppler waveform pattern. There was statistical difference in the mean portal blood flow velocity between G1 (17,23 ± 3,7cm/s) and G3 (13,66 ± 2,56cm/s), in the portal blood flow between G1 (32,69 ± 11,86mL/min/kg) and G2 (19,58 ± 7,68mL/min/kg) and between G1 and G3 (15,22 ± 8mL/min/kg), in the hepatorenal index between G2 (1,1 ± 0,29) and G3 (1,28 ± 0,22), in serum levels of alkaline phosphatase (ALP) between G1 and G3, in levels of gamma glutamyltranspeptidase (GGT) between G1 and G2 and in levels of cholesterol between G1 and the other groups. There was no statistical difference in the portal vein congestion index, hepatic artery resistance index, portal vein diameter and area and on serum levels of alanine aminotransferase (ALT) and triglycerides between the groups. It was concluded that obesity may be responsible for the development of parenchymal and hemodynamic changes in dog's liver